Left ventricular stiffness predicts outcome in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation. Issue 1 (25th October 2016) - Conte, Lorenzo; Fabiani, Iacopo; Pugliese, Nicola R.; Giannini, Cristina; La Carruba, Salvatore; Angelillis, Marco; Spontoni, Paolo; De Carlo, Marco; Petronio, Anna Sonia; Di Bello, Vitantonio
Abstract : Objectives: Assessment of the prognostic role of left ventricular stiffness (LVS) in patients with aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI). Methods: We performed a complete two‐dimensional transthoracic echocardiographic study before and after TAVI in patients with severe AS at high surgical risk. In order to assess LVS, we measured LV end‐diastolic pressure (EDP) invasively during TAVI and LV end‐diastolic volume (EDV) by means of echocardiography. We defined LVS as the EDV indexed by body surface area at an EDP of 20 mm Hg (EDVI20 ). Our aim was to assess the impact of LVS on one‐year all‐cause mortality after TAVI. Results: One hundred sixty‐six patients undergoing TAVI (64% female; mean age 82.7 ± 5.1 years) were enrolled. Seven patients died within the first 30 days after TAVI and 21 within 1 year. Overall follow‐up duration was 580 ± 478 days. At multivariate analysis, independent predictors of 1‐year all‐cause mortality were moderate‐to‐severe paravalvular leak (PVL; HR 4.7, 95% confidence interval [CI] 1.9‐11, P= .0003), female gender (HR 3.5, 95% CI 1.0‐12, P =.045), and EDVI20 (HR 0.94, 95% CI 0.90‐0.98, P= .015). In particular, patients with higher LVS (EDVI20 ≤48 mL/m 2 ) had a 1‐year mortality of 26.9% vs 7.4% in patients with lower LVS (EDVI20 >48 mL/m 2 ; HR 4.2, 95% CI 1.6‐10.6, P= .0007). Patients with higher LVS who developed moderate‐to‐severe PVL had the worst outcome (incremental chi‐square test, P= .014). Conclusion: In patients with AS, an increased LVS has a negative prognostic impact. Development of significant PVL in patients with higher LVS had an incremental adverse effect.